The development of trade policies in the Asia and Pacific region over the past 30 years since 1989 - Masahiro Hayafuji (World Trade Organization (WTO), 2020)
This paper reviews the main developments of trade and related policies and measures in the Asia and Pacific region during the 30 years since establishment, in 1989, of the Trade Policy Review Mechanism (TPRM). The objectives of the TPRM include facilitating the smooth functioning of the multilateral trading system by enhancing the transparency of WTO Members' trade policies. Reviews take place in the General Council, operating as the Trade Policy Review Body as peer-group assessments. This paper aims to identify the main trade liberalization/reform measures adopted over the 30 years and, to the extent possible, their developments, including adoption and abolition. The main source of information is the documentation used for the WTO trade policy reviews (TPRs) of 30 Members within the Asia-Pacific region, in particular, the reports by the Secretariat. Between 1989 and August 2019, 132 reviews for these Members were conducted; all documents used for the TPRs are available in the public domain.
Keywords: F13; F14; F61; 330; trade policy review; trade policies; trade restrictions; trade facilitation